2022
DOI: 10.3390/jof8060628
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Containing Compounds from Endophytic Fungi: Sources, Structures and Bioactivities

Abstract: Endophytic fungi have attracted increasing attention as an under-explored source for the discovery and development of structurally and functionally diverse secondary metabolites. These microorganisms colonize their hosts, primarily plants, and demonstrate diverse ecological distribution. Among endophytic fungal natural products, sulfur-containing compounds feature one or more sulfur atoms and possess a range of bioactivities, e.g., cytotoxicity and antimicrobial activities. These natural products mainly belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The endophytic fungus is now serving as a promisingly strategic natural bioresource for the discovery of novel natural products with interesting chemical structures and versatile biological activities (Fan et al, 2022 ). In particular, it was well-respected as a treasure house for developing novel antibacterial agents (Cruz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The endophytic fungus is now serving as a promisingly strategic natural bioresource for the discovery of novel natural products with interesting chemical structures and versatile biological activities (Fan et al, 2022 ). In particular, it was well-respected as a treasure house for developing novel antibacterial agents (Cruz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The endophytic fungus has now be considered auspiciously deliberate natural bioresource for the innovations of novel phytochemicals with diverse chemical moieties and flexible therapeutic applications (Fan et al, 2022). Further , it has been reported that it is rich deposits of house for discovering novel antibacterial compounds (Cruz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al reported 143 new sulfur-containing compounds that were reported from 1985 to 2022 and their fungal producers, plant sources, chemical structures, and bioactivities. These natural products mainly belong to the classes of polyketides, nonribosomal peptides, terpenoids, and hybrids [42].…”
mentioning
confidence: 99%